Pathways From HIV-Related Stigma, Racial Discrimination, and Gender Discrimination to HIV Treatment Outcomes Among Women Living With HIV in Canada: Longitudinal Cohort Findings - Malama, Kalonde; Logie, Carmen H; Sokolovic, Nina; Skeritt, Lashanda; O'Brien, Nadia; Cardinal, Claudette; Gagnier, Brenda; Loutfy, Mona; Kaida, Angela; de Pokomandy, Alexandra (Journal of acquired immune deficiency syndromes (1999), 2023)
HIV-related stigma, gender discrimination, and racial discrimination harm mental health and hamper HIV treatment access for women living with HIV. Maladaptive coping strategies, such as substance use, can further worsen HIV treatment outcomes, whereas resilience can improve HIV outcomes. We examined resilience and depression as mediators of the relationship between multiple stigmas and HIV treatment outcomes among women living with HIV. Ontario, British Columbia, and Quebec, Canada. We conducted a longitudinal study with 3 waves at 18-month intervals. We used structural equation modeling to test the associations of multiple stigmas (HIV-related stigma, racial discrimination, and gender discrimination) or an intersectional construct of all 3 stigmas at wave 1 on self-reported HIV treatment cascade outcomes (≥95% antiretroviral treatment [ART] adherence, undetectable viral load) at wave 3. We tested depression and resilience at wave 2 as potential mediators and adjusted for sociodemographic factors. There were 1422 participants at wave 1, half of whom were Black (29%) or Indigenous (20%). Most participants reported high ART adherence (74%) and viral suppression (93%). Racial discrimination was directly associated with having a detectable viral load, while intersectional stigma was directly associated with lower ART adherence. Resilience mediated associations between individual and intersectional stigmas and HIV treatment cascade outcomes, but depression did not. Racial discrimination was associated with increased resilience, while intersectional and other individual stigmas were associated with reduced resilience. Race, gender and HIV-related stigma reduction interventions are required to address intersectional stigma among women living with HIV. Including resilience-building activities in these interventions may improve HIV treatment outcomes.